The moderating effect of employee growth climate on the relationship between work engagement and job outcomes among plantation workers in North Sumatra, Indonesia - Rahmadani, Vivi Gusrini; Schaufeli, Wilmar B.; Fauzia, Rahma; Nazriani, Dina (Frontiers in Psychology, 2022)
The current study investigates the moderating effect of employee growth climate on the relationship between work engagement and job outcomes among plantation workers in North Sumatra, Indonesia. Three individual-level job outcomes are investigated, namely, intra-role behavior, employee learning, and innovative work behavior. Six hundred and seven Indonesian plantation workers from one of the biggest palm oil plantations in Indonesia participated. Work engagement and employee growth climate were positively related to the three types of job outcomes, as expected. Furthermore, the relationship between work engagement-intra-role behavior and work engagement-innovative work behavior was moderated by employee growth climate. However, no moderating effect of employee growth climate was observed for the relationship between work engagement-employee learning.